Exposure to tremolite asbestos and respiratory health in Swedish dolomite workers. Issue 10 (1st October 2001) - Seldén, A I; Berg, N P; Lundgren, E A L; Hillerdal, G; Wik, N-G; Ohlson, C-G; Bodin, L S
Abstract : OBJECTIVES: Deposits of carbonate rock like limestone and dolomite may contain tremolite asbestos. This study assessed the exposure to tremolite asbestos and the respiratory health of Swedish dolomite workers. METHODS: 95% of 137 eligible workers at two dolomite producing companies completed a self administered questionnaire that included questions on respiratory symptoms and were examined with spirometry as well as chest radiography. Total exposure to dust was gravimetrically measured and the tremolite asbestos content of the dust was assessed with polarisation and phase contrast microscopy. RESULTS: Dolomite dust concentrations were moderate (median 2.8 mg/m 3 ) and tremolite asbestos concentrations were generally below the limit of detection (<0.03 fibres/ml). Somewhat higher values, around 0.1 fibres/ml, were obtained in manual stone sorting and bagging. Respiratory symptoms suggestive of chronic bronchitis were more related to smoking than to estimates of individual exposure to dust. The mean vital capacity was 0.2 l lower than expected after adjustment for sex, age, height, and smoking but the decline in lung function was not associated with current or cumulative exposure to dust in a clear cut way. Two definite cases of pleural plaques and one possible case of simple pneumoconiosis were noted, but the plaques could not be attributed exclusively to exposure to tremolite asbestos. CONCLUSIONS: Dolomite mining and milling may indeed entail low levels of exposure to tremolite asbestos, but this exposure was not a strong determinant of respiratory symptoms, lung function, or pneumoconiosis in exposed Swedish workers. This was true also for dolomite dust. The hazards of exposure to tremolite asbestos may vary across deposits, however, and additional studies at other sites of carbonate rock exploitation are warranted.